The development of peer networks and academic performance in learning communities in higher education. (August 2022) - Brouwer, Jasperina; de Matos Fernandes, Carlos A.; Steglich, Christian E.G.; Jansen, Ellen P.W.A.; Hofman, W.H. Adriaan; Flache, Andreas
Abstract: In learning communities, students share their knowledge which might contribute to academic performance. This study disentangles peer selection from influence processes in modelling first-year students' academic performance after the transition to university. Longitudinal peer network data were obtained from 95 bachelor students at two time points in a social sciences study programme with eight learning communities. Using co-evolution modelling in RSiena, we found that students help each other more often when they are already friends and students who help each other academically are more likely to become friends. The higher a student performs, the more often the student is selected as a friend or as an academic helper and the more often this higher-performing student initiates friendship and academic help relationships. Although learning communities are often implemented to enhance academic performance, we did not find evidence that peer relationships in learning communities influence academic performance. Highlights: The higher university students perform, the more often they are approached for academic help and friendships. Higher performing university students initiate more often academic help and friendship relationships. University students help each other more often when they are friends and vice versa. Peers did not influence university students' academic performance in a learning environment with learning communities. Segregation based on academic performance can emerge in peer networks within and beyond learning communities.